Factors Affecting the Dividend Payout Ratio of Kompas100 Companies Listed on the Indonesia Stock Exchange for the 2018–2022 Period - Kamila, Nurul; Aji, Ditya Saputro (Westscience Press, 2025)
This study aims to determine the effect of Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Equity (ROE) on Dividend Payout Ratio (DPR) in companies in the Kompas100 index listed on the Indonesia Stock Exchange for the period 2018-2022. The sample selection technique in this study used purposive sampling technique and the samples collected amounted to 30 companies. Data analysis using the SPSS program. Based on the t test, the results of this study indicate that Debt to Equity Ratio (DER) has a negative and significant effect on Dividend Payout Ratio (DPR). Return on Assets (ROE) has a positive and significant influence on the Dividend Payout Ratio (DPR). Meanwhile, Current Ratio (CR) has no effect on Dividend Payout Ratio. Based on the F test, Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Equity (ROE) simultaneously have a significant effect on Dividend Payout Ratio (DPR).